PEMANFAATAN GOOGLE CLASSROOM UNTUK PROGRAM REMIDIAL ONLINE PADA PEMBELAJARAN SEJARAH - Rika Afrianto; Fahruddin Fahruddin (Jurnal Pendidikan Sejarah Indonesia, 2022)
The purpose of the study was to explain 1) the use of Google Classroom for online remedial programs on online history learning, 2) the utilization of features in Google Classroom for remedial implementation on online history learning. This research uses descriptive qualitative research methods. Data was collected from this study using journal articles and related books. While the data analysis used includes data collection, data reduction, presentation of data, and verifying of the resulting data. The object of this research is the online remedial program through Google Classroom in historical learning. The results of this study show that 1) the use of Google Classroom in online history learning results in more interesting learning for students, 2) the implementation of remedial programs in historical learning that use Google Classroom facilitates teachers to be able to make interesting questions, create quizzes and make assignments to make the impression of historical learning more interesting, with it, students will be more enthusiastic in learning history.Tujuan penelitian adalah untuk menjelaskan 1) penggunaan Google Classroom untuk program remedial online pada pembelajaran sejarah online, 2) pemanfaatan fitur-fitur pada Google Classroom untuk pelaksanaan remedial pada pembelajaran sejarah online. Penelitian ini menggunakan metode penelitian deskriptif kualitatif. Data dikumpulkan dari penelitian ini menggunakan artikel jurnal dan buku terkait. Sedangkan analisis data yang digunakan meliputi pengumpulan data, reduksi data, penyajian data, dan verifikasi data yang dihasilkan. Objek penelitian ini adalah program remedial online melalui Google Classroom pada pembelajaran sejarah. Hasil penelitian ini menunjukkan bahwa 1) penggunaan Google Classroom dalam pembelajaran sejarah online menghasilkan pembelajaran yang lebih menarik bagi siswa, 2) penerapan program remedial dalam pembelajaran sejarah yang menggunakan Google Classroom memfasilitasi guru untuk dapat membuat pertanyaan yang menarik, membuat kuis dan membuat tugas agar kesan belajar sejarah lebih menarik, dengan itu siswa akan lebih semangat dalam belajar sejarah.